The value of grain added to sorghum silage at ensiling - Smith, E.F.; Ward, G.M.; Richardson, D.; Perry, H.B. (Kansas Agricultural Experiment Station, 2011)
This experiment was to determine the value of sorghum grain, whole and ground, added to sorghum silage at 15% of the forage green weight at ensiling. The design was as follows: Treatment 1-No grain. Treatment 2-Ground sorghum grain fed when silage was fed Treatment 3-Whole sorghum grain added to silage while ensiling, with water added to bring the silage back to original moisture content. Treatment 4- Ground sorghum grain added to silage while ensiling and water added to bring silage moisture content to original.
Keywords: Beef; Sorghum silage; Daily gain